The Role of Technology In Shaping The Creativity of Islamic Education Teachers In The Era of Merdeka Curriculum In Elementary Schools - Munawir, Munawir; Aabidah, Annisah Dzakiyyah; Alfizzahra, Dinda Ainun (Peneliti.net, 2024)
This study uses a qualitative approach by conducting descriptive analysis that has integrated technology in their learning. The collected data were analyzed using descriptive analysis method. The results of the study show that technology can play an important role in shaping the creativity of PAI teachers. In the context of the Independent Curriculum, technology gives PAI teachers access to various digital resources, such as interactive learning materials, videos, and game-based learning applications. The use of this technology provides an opportunity for teachers to present learning materials in a more interesting and innovative way, so as to increase their creativity in designing effective learning strategies. This research shows that technology has a significant role in shaping the creativity of PAI teachers in the Independent Curriculum era in MI/SD. With the right use of technology, PAI teachers can develop innovative and interesting learning strategies for students, increasing their participation and understanding in Islamic education learning. However, challenges related to access to and skills in technology need to be addressed to ensure effective use of technology in the context of PAI learning.